Smoking a Dangerous Addiction: A Systematic Review on an Underrated Risk Factor for Oral Diseases - Naveed Ahmed (MDPI AG, 2021)
Despite growing knowledge of the adverse effects of cigarette smoking on general health, smoking is one of the most widely prevalent addictions around the world. Globally, about 1.1 billion smokers and over 8 million people die each year because of cigarette smoking. Smoking acts as a source for a variety of oral and systemic diseases. Various periodontal issues such as increased pocket depth, loss of alveolar bone, tooth mobility, oral lesions, ulcerations, halitosis, and stained teeth are more common among smokers. This systematic review was conducted according to the guidelines from PRISMA, and research articles were retrieved from the Web database sources on 31 May 2021. The quality of research articles was ensured by the type of evidence from combined schema incorporating as schema-13 evidence type description, Cochrane health promotion and public health field (CHPPHF), and the health gains notation framework-14 screening question for quality assessment of qualitative and quantitative studies. Smokers have been found to have bleeding on probing, periodontal pockets, and clinical attachment loss compared to nonsmokers. Oral and respiratory cancers are among the most lethal known diseases caused by cigarette smoking and other commonly occurring sequelae such as stained teeth, periodontal diseases, etc.